Kinetic Parameters of Nitrate Absorption by Adult Coffee Trees - Avellaneda Bohórquez, César Augusto; Martinez, Herminia Emilia Prieto; Santos, Ricardo Henrique Silva (Frontiers in Sustainable Food Systems, 2021)
Nitrogen, the most demanded nutrient by coffee plants, has a rate of recovery from the soil of about 50%. Because of that high doses of nitrogenous fertilizers are used to reach high production, and consequently high amounts of N are lost to the environment. Knowing the kinetic parameters of nitrate (NO3-) absorption over the fruit development cycle is important as a mean of achieve more adjusted fertilizer doses and better recovery rates for the N applied as fertilizers. This study aimed determining the kinetic parameters of NO3- absorption in different development stages of fruits from adult coffee plants. The kinetic parameters Vmax and Km were determined in a low production year, at the pinhead (PH), rapid expansion (RE), grain filling (GF), and maturation (MT) stages. One month before each kinetics assay, lateral roots of eight plants were excavated and wrapped into non-woven fabrics grow cylinders filled in with vermiculite to produce absorbent roots. On the assay day, the roots were washed and immersed into a container with 1 L of 90 μmol L−1 NO3- solution. Sampling began one and a half hours after that, and was taken every hour over 7 h. Data on NO3- depletion were used to calculate the absorption kinetic parameters Vmax and Km. In a low production year the Vmax ranged from 0.14 to 0.72 μmol g−1 h−1 in a root fresh matter basis and Km from 6.47 to 50.31 μmol L−1. The Vmax values were highest at the PH and MT stages; the lowest absorption rate was recorded at GF and Km was lowest at RE. As at the RE stage of fruits Vmax shows a positive correlation with grain production, adequate nitrogen availability must be ensured before this phase to not to affect coming coffee production.